Design Analysis of Closed Vessel for Power Cartridge Testing - Bhupesh Ambadas PARATE (Wojskowa Akademia Techniczna, 2019)
This paper discusses the design analysis of closed vessel (CV) for power cartridge application in water-jet disruptor. In this article, various design theories are presented in which the vessel is subjected to internal pressure. CV is a kind of pressure vessel utilized to evaluate the performance of power cartridge used for water-jet application. It is a test vessel which generates pressure - time profile by burning the propellant. Energy derived from burning of the propellant of power cartridge aids in neutralizing Improvised Devices (IED's). This energy creates high water-jet plume in the disruptor. In order to evaluate various performance parameters of the cartridge, CV design plays a vital role in the research and development activities, including, development, life trials, production, lot proof trials and life extension / life revision trials. CV is one of the methodologies / techniques from which energy generated is measured in terms of the maximum pressure (Pmax) and the time to maximum pressure (TPmax). This paper also discusses about various design aspects using the finite element method (FEM) and their comparative results with different design theories.In the light of these theoretical, numerical, and experimental works, it was recommended that octahedral stress theory or van Mises theory should be used for vessel design. This satisfies the designer requirements. FEM analysis tool helps in reducing time & development cost.
Keywords: Wybrane aspekty projektowania komory manometrycznej